Negative regulators of STAT3 signaling pathway in cancers - Wu M; Song D; Li H; Yang Y; Ma X; Deng S; Ren C; Shu X (Cancer Management and Research, 2019)
Moli Wu,1,2,* Danyang Song,1,* Hui Li,1 Yang Yang,1 Xiaodong Ma,1 Sa Deng,1 Changle Ren,3 Xiaohong Shu11College of Pharmacy, Dalian Medical University, Dalian 116044, People’s Republic of China; 2College of Basic Medical Sciences, Dalian Medical University, Dalian 116044, People’s Republic of China; 3Surgery Department of Dalian Municipal Central Hospital, Dalian Medical University, Dalian 116033, People’s Republic of China *These authors contributed equally to this workAbstract: STAT3 is the most ubiquitous member of the STAT family and involved in many biological processes, such as cell proliferation, differentiation, and apoptosis. Mounting evidence has revealed that STAT3 is aberrantly activated in many malignant tumors and plays a critical role in cancer progression. STAT3 is usually regarded as an effective molecular target for cancer treatment, and abolishing the STAT3 activity may diminish tumor growth and metastasis. Recent studies have shown that negative regulators of STAT3 signaling such as PIAS, SOCS, and PTP, can effectively retard tumor progression. However, PIAS, SOCS, and PTP have also been reported to correlate with tumor malignancy, and their biological function in tumorigenesis and antitumor therapy are somewhat controversial. In this review, we summarize actual knowledge on the negative regulators of STAT3 in tumors, and focus on the potential role of PIAS, SOCS, and PTP in cancer treatment. Furthermore, we also outline the STAT3 inhibitors that have entered clinical trials. Targeting STAT3 seems to be a promising strategy in cancer therapy.Keywords: cancer, STAT3 signaling, PIAS, SOCS, PTP, negative regulators